The effects of a single intravenous injection of novel activin A/BMP-2 (AB204) on toxicity and the respiratory and central nervous systems. (2nd July 2016) - Yoon, Byung-Hak; Lee, Jae Hyup; Na, Kyuheum; Ahn, Chihoon; Cho, Jongho; Ahn, Hyun Chan; Choi, Jungyoun; Oh, Hyosun; Kim, Byong Moon; Choe, Senyon
Abstract: The purpose of this study was to determine the effects of a single intravenous injection of a novel osteoinductive material, activin A/BMP-2 (AB204), to rodents on toxicity and their respiratory functions and central nervous system (CNS). A single intravenous injection of AB204 was given to Sprague–Dawley (SD) rats in doses of 0, 0.625, 2.5 and 10 mg/kg to observe the mortality rate, the general symptoms for 14 days. The experimental groups were also given 0.2, 0.4 and 0.8 mg/kg of AB204, respectively, and the respiration rate, the tidal volume and the minute volume were measured for 240 min. The experimental groups of imprinting control region (ICR) mice were given a single intravenous injection of 0.2, 0.4 and 0.8 mg/kg of AB204, respectively. Their body temperature was taken and general behaviors were observed to evaluate the effect of AB204 on the CNS for 240 min. The study on toxicity of a single intravenous injection found no death or abnormal symptoms, abnormal findings from autopsy, or abnormal body weight gain or loss in all the experimental groups. No abnormal variation associated with the test substance was observed in the respiration rate, the tidal volume, the minute volume, body temperature or the general behaviors. On the basis of these results, the approximate lethal dose of AB204 for a single intravenous injection exceeds 10 mg/kg for SD rats and a single intravenous injection of ≤0.8 mg/kg AB204 has no effect on their respiratory system for SD rat and no effect on their CNS for ICR mice.